Histórico do Campus e as patologias das fachadas dos prédios voltados para a Avenida Roraima - UFSM - Müller, Siomara Ribeiro (2010)
The study of pathological manifestations in buildings becomes increasingly important, especially when it comes to property which is tipped over. The Federal University of Santa Maria appears in a historical context of internalization of higher education in our country, in the 60s. The reflection of this intention was to elaborate a Master Plan which was partially implemented over the years. Important aspect concerns the architectural and cultural heritage represented by the Campus, which covers the City University Prof. José Mariano da Rocha Filho, the only urban set representative of the Internacional Style in Santa Maria and even at the level of Brazil, which is gradually being mischaracterized. This paper addresses the pathologies involved in the deterioration of the facades of buildings facing the Avenida Roraima, the main access to the Campus and axle office of the Master Plan that are unique and the most degraded. Only by knowing the factors which impact on these buildings, which are in the minds of "Holy-Mariens" (santa-marienses), you can plan your maintenance, which based the premise work. Therefore, we conducted field surveys to obtain an overview of the pathological processes involved in the degradation of buildings, studying their manifestations and inter-relationships through data tabulation. It was found that most complaints are superficial, highlighting the neglect and lack of preventive maintenance of buildings.